Perlindungan Anak sebagai Korban dengan Orang Tua Kombatan Teroris di Balai Rehabilitasi Anak Membutuhkan Perlindungan Khusus Handayani Kementerian Sosial - Aprilia Heriati; Chazizah Gusnita (Universitas Budi Luhur, 2019)
The case of terrorism involving a child as a victim with parent of terrorist combatants is a new form of violent crime in the household, where the child is involved by the head of the household and indoctrinated to engage in a heresy by doing things which not taught in any religion. The revealed of child’s identitiy to the community then forming a stigma, thus giving a threat to the rights of children to be protected. The research uses the victimology theory to explain that there is a closeness between children as victims with parents as perpetrators. The study used a qualitative approach as a research method by interviewing five informants. The results showed that there are several factors that caused children become victims of parent combatants terrorist, they are: form of child care pattern, social dysfunction role as child, protection obtained by children based on the implementation of child protection law, terrorism law, and the law of combating terrorism in the form of deradicalisation program for children, and the fulfillment of the rights of children.